Self-Efficacy, Students’ Perception of Active Learning Strategies, and Problem-Solving Skills in Mathematics - Jane Myca Millana; Kyra Marie Bersamina; Meraflor Zapanta; Claris Amarille; Abdul J Jamara (Goodwood Publishing, 2026)
Purpose: This study aimed to determine whether self-efficacy and students’ perception of active learning strategies predict problem-solving skills in mathematics among first-year BSED Mathematics students. Research Methodology: A quantitative descriptive-correlational research design was used. The respondents were 83 first-year Bachelor of Secondary Education majoring in Mathematics students from Davao del Norte State College. The research tools included the Self-efficacy Questionnaire, the Students’ Perception of Active Learning Strategies Questionnaire, and a researcher-made problem-solving skills test. Results: Students showed evident self-efficacy and perception of active learning strategies, and above-average problem-solving skills. Researchers found no significant relationship between self-efficacy and problem-solving skills, and students' perception of active learning strategies and problem-solving skills. The study also revealed that no predictive effect was found between the independent and dependent variables. Conclusions: The study concluded that self-efficacy and students’ perception of active learning strategies do not significantly predict the problem-solving skills of first-year Bachelor of Secondary Education major in Mathematics students. Despite demonstrating high levels of self-efficacy and positive perceptions of active learning strategies, these factors were not significantly related to their problem-solving skills. This suggests that variables beyond self-efficacy and active learning strategies may have a greater influence on the development of problem-solving skills in mathematics. Limitations: The study was limited to first-year BSED Mathematics students from a single institution. Contributions: This study is useful in mathematics education, teacher education, and educational research.